The Manners, Stupid! In Search of the Keys of the Therapeutic Alliance from the Management of Dissatisfaction - Corominas Díaz, Antoni (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
The aim of this study is to determine the core factors of the therapeutic relationship in mental health, and therefore, the basis of a successful therapeutic alliance. The source of data analyzed includes surveys of patient satisfaction and the study of the main causes of patient’s complaints. Communication skills, attitudes and manners emerge as essentials when it comes to satisfactory relationships. The failure of the therapeutic alliance arises when patients feel that they have been roughly or wrongly treated and, even more, when they perceive a lack of involvement or effort by the therapist. A model of inverted pyramids is postulate in order to describe the apparently divergent values of patients and therapists. These include knowledge-technical skills, attitudes-empathy, and forms-manners. Also, three paradoxes are described that summarize the main challenges in the current framework of the therapeutic relationships.